Hierarchy in practice: Multilateral diplomacy and the governance of international security. Issue 1 (27th January 2016) - Pouliot, Vincent
Abstract: In today's world, a significant portion of international security politics is conducted through multilateral channels, often from the halls of international organisations such as the United Nations or NATO. This article theorises and empirically documents the production, reproduction, and contestation of local diplomatic hierarchies that practitioners often call 'international pecking orders'. According to conventional wisdom in IR, the sources of international hierarchies are primarily structural, stemming from the interstate distribution of (material) capabilities. Yet the growing prevalence of multilateral diplomacy in the governance of international security generates distinctive forms of social stratification organised around a struggle for diplomatic competence. As they pursue their instructions and manage security politics, state representatives posted to international organisations make use of the opportunities and constraints of a given situation and compete for rank through the display of practical know-how. The article illustrates this process by looking at how a key set of multilateral practices lend themselves to pecking order dynamics, from esprit de corps to reporting through brokering. By taking the multilateralisation of security politics seriously, the article shows that international hierarchy, far from an unobservable reality, is actually part of parcel of each and every practice that makes the world go round.